THEORETICAL PRINCIPLES OF EDUCATION OF CADETS’ MORAL RESISTANCE TOWARDS THE MANIPULATIVE INFLUENCE OF ENEMY PROPAGANDA - Zinyak, Ihor (Theoretical and Methodical Problems of Children and Youth Education, 2023)
The article examines the theoretical principles of raising cadets’ moral resistance towards the manipulative influence of enemy propaganda as an actual scientific and pedagogical problem. To solve the research tasks, the methods of analysis of scientific sources, comparison, generalization and systematization of the research problem, the study of pedagogical experience, and the identification of the structure of the moral stability of the future officer were used. Based on the analysis of philosophical, psychological and pedagogical literature, the generalization of empirical data on the research topic, advanced pedagogical experience, the concept of “education of cadets’ moral resistance towards the manipulative influence of enemy propaganda” was defined as an integrated personal quality, which consists in preserving and observing moral values in the conditions of tan aggressive environment, misinformation, manipulation of enemy propaganda, influence on the psyche, and determines the ability of the individual to resist actively and protect the freedom, democracy and sovereignty of Ukraine from external and internal threats. It has been established that enemy propaganda is a purposeful influence on the thoughts, feelings, consciousness and behaviour of citizens of another country with the aim of undermining their morale, solidarity, patriotism, trust in state institutions, imposing inferiority and weakness compared to other nations and states. Enemy propaganda is typified by goals (aggressive, defensive, negotiation), orientation (internal, external), methods of influence (rational, emotional, and manipulative) and mechanisms (dehumanization, desubjectivization, creating an image of the enemy, militarization), methods of dissemination (official, unofficial). The content structure of the education of moral stability has been developed, which includes cognitive, emotional-value, volitional and active components. The practical significance of the article is that its materials can be used in organizing educational work of military institutions of higher education, training of officer and teaching staff and cadets